Corrigendum to “Nuclear charge radii of germanium isotopes around N = 40” [Physics Letters B, 856 (2024)138867] (Physics Letters B (2024) 856, (S0370269324004258), (10.1016/j.physletb.2024.138867)) - Wang, S. J.; Kanellakopoulos, A.; Yang, X. F.; Bai, S. W.; Billowes, J.; Bissell, M. L.; Blaum, K.; Cheal, B.; Devlin, C. S.; Ruiz, R. F.Garcia; Han, J. Z.; Heylen, H.; et al. (Physics Letters B, 2024)
The authors regret to inform that an error was made in the funding numbers listed in the Acknowledgements section of the paper, which was made available online at 11 July 2024. The correct information for the acknowledge should be: We acknowledge the support of the ISOLDE collaboration and technical teams. This work was supported by the National Key R&D Program of China (Contract Nos. 2022YFA1605100, 2023YFA1606403), the National Natural Science Foundation of China (Nos:12027809,12350007); the BriX Research Program No. P7/12, FWO-Vlaanderen (Belgium), GOA 15/010 from KU Leuven; the UK Science and Technology Facilities Council grants ST/L005794/1 and ST/P004598/1; the German Federal Ministry of Education and Research (BMBF) Contracts No 05P18RDCIA, 05P21RDCI1, the Max-Planck Society, the Helmholtz International Center for FAIR (HIC for FAIR); the EU Horizon2020 research and innovation programme through ENSAR2 (No. 654002); the computing center RRZE of the Friedich-Alexander university Erlangen; and by the U.S. Department of Energy under Award Number DE-SC0013365 (Office of Science) and DE-SC0023175 (Office of Science, NUCLEI SciDAC-5 collaboration). The authors kindly request a corrigendum to replace the original text “We acknowledge the support of the ISOLDE collaboration and technical teams. This work was supported by the National Key R&D Program of China (Contract Nos. 2022YFA1604800, 2023YFA1606403), the National Natural Science Foundation of China (Nos:12027809,12350007); the BriX Research Program No. P7/12, FWO-Vlaanderen (Belgium), GOA 15/010 from KU Leuven; the UK Science and Technology Facilities Council grants ST/L005794/1 and ST/P004598/1; the German Federal Ministry of Education and Research (BMBF) Contracts No 05P18RDCIA, 05P21RDCI1, the Max-Planck Society, the Helmholtz International Center for FAIR (HIC for FAIR); the EU Horizon2020 research and innovation programme through ENSAR2 (No. 654002); the computing center RRZE of the Friedich-Alexander university Erlangen; and by the U.S. Department of Energy under Award Number DE-SC0013365 (Office of Science) and DE-SC0023175 (Office of Science, NUCLEI SciDAC-5 collaboration).” with the correct information. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2024-11-01